Economic Analysis of Thermal Insulation Systems - Csizmadi, Ivett; Győri, Barnabás (International Journal of Engineering and Management Sciences, 2017)
One of today’s most important problem of inadequate energy management. In Hungary, most of the buildings considered to be outdated in the building materials used and taking into account the construction technology. A significant part of the heat energy used for heating purposes before leaving the environment through the building envelope elements used in time. In our study we investigate whether an average house how much energy you can save the facade walls with insulation.